Economic evaluation of a healthy lifestyle intervention for chronic low back pain: A randomized controlled trial. (4th December 2018) - Williams, Amanda; van Dongen, Johanna M.; Kamper, Steven J.; O'Brien, Kate M.; Wolfenden, Luke; Yoong, Sze L.; Hodder, Rebecca K.; Lee, Hopin; Robson, Emma K.; Haskins, Robin; Rissel, Chris; Wiggers, John; et al.
Abstract: Background: Economic evaluations which estimate cost‐effectiveness of potential treatments can guide decisions about real‐world healthcare services. We performed an economic evaluation of a healthy lifestyle intervention targeting weight loss, physical activity and diet for patients with chronic low back pain, who are overweight or obese. Methods: Eligible patients with chronic low back pain ( n  = 160) were randomized to an intervention or usual care control group. The intervention included brief advice, a clinical consultation and referral to a 6‐month telephone‐based healthy lifestyle coaching service. The primary outcome was quality‐adjusted life years (QALYs). Secondary outcomes were pain intensity, disability, weight and body mass index. Costs included intervention costs, healthcare utilization costs and work absenteeism costs. An economic analysis was performed from the societal perspective. Results: Mean total costs were lower in the intervention group than the control group (‐$614; 95%CI: −3133 to 255). The intervention group had significantly lower healthcare costs (‐$292; 95%CI: −872 to −33), medication costs (−$30; 95%CI: −65 to −4) and absenteeism costs (‐$1, 000; 95%CI: −3573 to −210). For all outcomes, the intervention was on average less expensive and more effective than usual care, and the probability of the intervention being cost‐effective compared to usual care was relatively high (i.e., 0.81) at a willingness‐to‐pay of $0/unit of effect. However, the probability of cost‐effectiveness was not as favourable among sensitivity analyses. Conclusions: The healthy lifestyle intervention seems to be cost‐effective from the societal perspective. However, variability in the sensitivity analyses indicates caution is needed when interpreting these findings. Significance: This is an economic evaluation of a randomized controlled trial of a healthy lifestyle intervention for chronic low back pain. The findings suggest that a healthy lifestyle intervention may be cost‐effective relative to usual care.